Ballistic Trauma : A Practical Guide - Breeze, John; Penn-Barwell, Jowan G.; Keene, Damian; O'Reilly, David; Jeyanathan, Jeyasankar; Mahoney, Peter F. (Springer International Publishing : Imprint: Springer, 2017)
This revised fourth edition provides a concise guide to the clinical and operational issues surrounding the management of the ballistic casualty. This book utilises the knowledge and experience acquired by those dealing with ballistic trauma on a regular basis to help those who manage these patients less regularly. This book is a valuable reference tool for all medical and paramedical personnel involved in the care of patients with ballistic injury. It is especially relevant for consultants and senior trainees in surgery, anesthesia, and emergency medicine who are likely to be involved in the management of these unique injuries.
Keywords: Medicine.; Emergency medicine.; Critical care medicine.; Orthopedics.; Traumatology.; Vascular surgery.; elektronické knihy; electronic books